The involvement of Toll‐like receptor 9 in the pathogenesis of erosive autoimmune arthritis. Issue 9 (11th July 2018) - Fischer, Anita; Abdollahi‐Roodsaz, Shahla; Böhm, Christina; Niederreiter, Birgit; Meyer, Brigitte; Yau, Anthony C. Y.; Lönnblom, Erik; Joosten, Leo A. B.; Koenders, Marije; Lehmann, Christian H. K.; Dudziak, Diana; Krönke, Gerhard; et al.
Abstract: Endogenous nucleic acids and their receptors may be involved in the initiation of systemic autoimmune diseases including rheumatoid arthritis (RA). As the role of the DNA sensing Toll‐like receptor (TLR) 9 in RA is unclear, we aimed to investigate its involvement in the pathogenesis of autoimmune arthritis using three different experimental models of RA. The data obtained revealed involvement of TLR9 in the T cell‐dependent phase of inflammatory arthritis. In rats with pristane‐induced arthritis (PIA), TLR9 inhibition before disease onset reduced arthritis significantly and almost completely abolished bone erosion. Accordingly, serum levels of IL‐6, α‐1‐acid‐glycoprotein and rheumatoid factor were reduced. Moreover, in TLR9 −/− mice, streptococcal cell wall (SCW)‐induced arthritis was reduced in the T cell‐dependent phase, whereas T cell‐independent serum‐transfer arthritis was not affected. Remarkably, while TLR7 expression did not change during in vitro osteoclastogenesis, TLR9 expression was higher in precursor cells than in mature osteoclasts and partial inhibition of osteoclastogenesis was achieved only by the TLR9 antagonist. These results demonstrate a pivotal role for TLR9 in the T cell‐dependent phases of inflammatory arthritis and additionally suggest some role during osteoclastogenesis. Hence, endogenous DNA seems to be crucially involved in the pathophysiology of inflammatory autoimmune arthritis.